Avaliação da função endotelial de gestantes diabéticas através da dilatação mediada por fluxo da artéria braquial - Oliveira, Daniele Sparemberger (2017)
Introduction: Gestational diabetes is a potentially harmful disease for the mother and fetus during pregnancy. It is associated with higher risk of developing a hypertensive syndrome during pregnancy and maternal cardiovascular diseases, but also with increased risk of adverse fetal outcomes such as macrosomia and fetal death. Objectives: the aim was to evaluate endothelial function in pregnancies with and without gestational diabetes mellitus (GDM). Methods: this case control study measured endothelial function trough brachial artery flow mediated dilatation (FMD) using ultrasound, evaluating pregnant women between twenty and thirty six weeks gestation. Sample size was calculated to detect a difference of one standard deviation in FMD (90% power and alpha 0.05) between groups. Results: The study sample consisted of thirty-six patients in each group. The clinical and demographic characteristics were similar in both groups, although the glucose status and the basal body mass index (BMI) were significantly higher in the group of pregnant women with diabetes. Median FMD was significantly reduced in gestational diabetes group (18.3%, IQR: 11.9-23.3%) compared to the control group (9.7%, IQR: 5.7-14.1%; p<0.001), indicating impaired endothelial function. Cohen's d was 0.90 and the effect-size r was 0.41, which is considered a large Cohen’s Standard effect. Conclusions: Gestational diabetes is associated with endothelial dysfunction.